2016
DOI: 10.1063/1.4964887
|View full text |Cite
|
Sign up to set email alerts
|

Vector magneto-optical sensor based on transparent magnetic films with cubic crystallographic symmetry

Abstract: The concept of vector magneto-optical magnetometry is proposed and experimentally demonstrated. The key element of the vector magnetometer is a transparent high Faraday activity magnetic film with a cubic crystal lattice. Magnetocrystalline anisotropy of the film leads to the three dimensional trajectory of the film magnetization when the magnetization is rotated by the control magnetic field. It makes the magnetization sensitive to all three components of the external magnetic field. This field can be found f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…The magneto-optical reading in the flux-gate magnetometry provides additional functionality including vector character , and imaging and micrometer spatial resolution . In the absence of the reading coils in such magnetometers the Schottky noise can be avoided.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The magneto-optical reading in the flux-gate magnetometry provides additional functionality including vector character , and imaging and micrometer spatial resolution . In the absence of the reading coils in such magnetometers the Schottky noise can be avoided.…”
mentioning
confidence: 99%
“…The magneto-optical sensors are usually based on ferromagnetic metals (iron, nickel, cobalt, and their alloys) and ferrimagnetic dielectrics represented by bismuth iron-garnet films. The latter are very efficient since they have quite high specific Faraday rotation and optical transparency in the visible and near-infrared spectral ranges. , Moreover, the monocrystalline iron-garnet films with in-plane magnetic anisotropy demonstrate very high magnetic susceptibility that makes them valuable for sensing. ,,, …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The examined problem also contains a weak measurable field h ≪ H with an arbitrary direction and thus having arbitrary h = {h x , h y , h z } spatial components. We consider an iron garnet film with high cubic magnetic anisotropy, for example (Bi 1.1 Lu 1.45 Pr 0.2 Tm 0.2 Gd 0.05 )(Fe 3.5 Al 0.8 Ga 0.7 )O 12 [10] or Tm 3 Fe 4.3 Sc 0.7 O 12 [29]. Due to high anisotropy the dynamics of the magnetization M vector under the H impact is rather complicated in such films and, moreover, M direction does not coincide with H even in the quasi-static case (ω ≪ γH).…”
Section: Dynamics Of Magnetization In Magnetic Film With Strong Aniso...mentioning
confidence: 99%
“…The flux-gate magnetometry is based on the measurement of the medium magnetization under the impact of the external magnetic field. It was recently shown that contactless magneto-optical (MO) reading of the magnetization state allows one to measure magnetic fields in vector format [10,11] with micrometer spatial resolution [12]. Therefore, the enhancement of the MO effects is a vital problem of the flux-gate magnetometry.…”
Section: Introductionmentioning
confidence: 99%